Impact of early arterial-phase multidetector CT in blunt spleen injury: a clinical outcomes-oriented study - Yu-Hao Wang; Yu-Tung Wu; Huan-Wu Chen; Yu-San Tee; Chih-Yuan Fu; Chien-Hung Liao; Chi-Tung Cheng; Chi-Hsun Hsieh (BMC Medical Imaging)
Abstract Background Blunt spleen injuries (BSI) present significant diagnostic and management challenges in trauma care. Current guidelines recommend arterial-phase contrast-enhanced multidetector computed tomography (CT) for a detailed assessment. However, the direct impact of add-on arterial phase CT on clinical outcomes remains unclear. This study investigated the impact of early arterial-phase imaging via multidetector CT on the clinical outcomes of patients with blunt splenic injuries. Methods A retrospective case-control study was conducted to analyze the data of adult patients with BSI treated at a single institution between 2019 and 2022. Patients were divided based on the CT phase performed: portal vein phase only or add-on arterial phase. Management methods were divided according to the initial treatment intent: nonoperative management observation (NOM-Obs), transarterial embolization (TAE), and splenectomy. NOM failure refers to either NOM-Obs or TAE failure leading to splenectomy. NOM-Obs failure refers to cases initially managed with observation only, but later requiring either TAE or splenectomy. Transarterial embolization (TAE) failure refers to cases initially treated with TAE, but subsequently requiring splenectomy. Inverse probability of treatment weighting (IPTW) was used to balance baseline differences and compare outcomes between the two groups. Results Of 170 patients assessed, 147 met the inclusion criteria and were divided into two groups: those receiving portal vein phasic-only CT (N = 104) and those receiving add-on arterial phasic CT (N = 43). The overall NOM failure rate was 3.0% (4/132), the NOM-OBS failure rate was 6.7% (4/60), and the TAE failure rate was 4.1% (3/73). After adjusting for covariates using inverse probability of treatment weighting (IPTW), the comparison between the add-on arterial phase and portal phase CT groups revealed similar overall NOM failure rates (3.0% vs. 2.2%, p = 0.721), NOM-OBS failure rates (3.8% vs. 6.2%, p = 0.703), and intra-abdominal bleeding-related mortality rates (4.8% vs. 2.1%, p = 0.335). Among the 43 patients who underwent add-on arterial CT, only one was diagnosed with a tiny pseudoaneurysm (0.7 cm) attributable to the inclusion of the arterial phase. Conclusion Dual-phase CT within 24 h of presentation offers no added value over single-phase CT in managing blunt splenic injuries in terms of clinical outcomes.